Grasp on next generation security operation centre (NGSOC): - Dun, Yau Ti; Mohd Faizal, Ab Razak; Mohamad Fadli, Zolkipli; Bee, Tan Fui; Ahmad Firdaus, Zainal Abidin (Semnan University, 2021)
With the growing number of cyber security threats affecting the business environment of many organizations, especially the IT environment. With the growing number of cyber security threats affecting the business environment of many organizations, especially the IT environment. Managed protection systems, including SOC, are highly sought after. Managed protection systems, including SOC, are highly sought after. The problem with SOC is that when building up their own SOC or hiring a third-party to provide SOC, organizations are not able to apply adequate criteria or standard frameworks. The aim of the study is to lay the foundations for developing a modern system of systematic operation centers for the next generation (NGSOC) for IIoT climate. This paper contains thorough, qualitative literature survey on the implementation of a Security Operation Centre (SOC). A comparative study is carried out using a variety of previous research sources and a literature review. The findings from the report show that previous research is not adequately guided, especially in the safety and technical aspects of the building block of the SOC. It is hoped that by proposing the framework, cybersecurity threat prevention and identification would be strengthened even further. The success of the NGSOC will ultimately be determined by the integration of individuals, procedure, and technology.